2008
DOI: 10.1103/physrevlett.100.157201
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Intrinsic Ferromagnetic Interactions of Isolated and Paired Co Dopant Atoms inZn1xCoxOwith High Structural Perfection

Abstract: We report element specific structural and magnetic investigations on Zn(1-x)Co(x)O epitaxial films using synchrotron radiation. Co dopants exclusively occupy Zn sites as revealed by x-ray linear dichroism having an unprecedented degree of structural perfection. Comparative magnetic field dependent measurements by x-ray magnetic circular dichroism and conventional magnetometry consistently show purely paramagnetic behavior for isolated Co dopant atoms with a magnetic moment of 4.8 (mu B). However, the total mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
130
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(155 citation statements)
references
References 13 publications
24
130
1
Order By: Relevance
“…The oxidation state of Co is therefore inferred to be 2þ in Co:ZnO, 28 in agreement with our X-ray absorption measurements, suggesting that Co substitutes for Zn in the lattice uniformly. 13 Figure 5(a) shows that the O a/b ratio increases slightly on approaching the interface between the Co:ZnO layer and the Al 2 O 3 . Since these measurements have relatively large errors, a more sensitive approach was used involving measurements of the threshold energy of the O K-edge to follow the change in chemical environment across the interface, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation state of Co is therefore inferred to be 2þ in Co:ZnO, 28 in agreement with our X-ray absorption measurements, suggesting that Co substitutes for Zn in the lattice uniformly. 13 Figure 5(a) shows that the O a/b ratio increases slightly on approaching the interface between the Co:ZnO layer and the Al 2 O 3 . Since these measurements have relatively large errors, a more sensitive approach was used involving measurements of the threshold energy of the O K-edge to follow the change in chemical environment across the interface, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thin epitaxial films of Co:ZnO were deposited onto cplane sapphire substrates using PLD 13,14 and RMS. 5 Careful pre-characterization using x-ray diffraction, XAS, XLD, XMCD, and SQUID has been performed before for the PLD-10 (Refs.…”
Section: Methodsmentioning
confidence: 99%
“…Ney et al 53 have demonstrated that highly perfect Co-doped epitaxial films, for example, are purely paramagnetic, with cobalt occupying zinc sites and no sign of anything other than weak antiferromagnetic Co-O-Co nearest-neighbor superexchange. Droubay et al 54 show that Mn-doped epitaxial films are paramagnetic, with Mn substituting for Zn, and no moments on either oxygen or zinc.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 and references therein) and confirmed by X-ray linear dichroism (XLD) measurements. 13 However, some observations do not completely conform to the scenario where all impurities occupy Zn substitutional sites in ZnO. X-ray absorption near-edge structure spectroscopy (XANES) 4,14 and X-ray photoelectron spectroscopy (XPS) 15 experiments have shown that Mn impurities can be incorporated in ZnO with charge states of up to 4+.…”
Section: Introductionmentioning
confidence: 97%